A compreensão do Reino à luz da representação de Deus como Pai a partir da oração do Pai-Nosso. - Cerqueira, Kinno Alves (2020)
Kingdom of God is an expression present in the Bible, in Christian theologies and in the imaginary of churches since time immemorial and its imaginary strength is an inexhaustible source of meanings. Starting from the perception that the Our Father's prayer present in the Gospel according to Matthew (Mt 6,9-13) is inhabited by a hermeneutic key that demands an interpretation of the Kingdom pleaded in the light of the invoked Father, it was aimed, with this research, discuss the representations of the human father and of God as Father in the Bible, underlining the continuities and discontinuities between human and divine fatherhoods. Thereby, proceeding to an interpretation of the biblical notion of the Kingdom of God in the light of the representation of God as Father. The methodology used consisted of analysis of biblical texts and bibliographic consultation. It was noted that human and divine paternities are, in the Bible, fluid images whose sliding of senses depends on the contexts in which they appear. Unlike the human father, who becomes a father, God is made Father by those who resemble him in the practice of mercy, justice and love. The Father's face outlined above succeeded in opening a window through which the biblical representations of God as Father are conceived as a myself rooted in the desire for freedom and the Kingdom of the Father, as a confession of the desire for the disappearance of God and by the affirmation of the subject, the emancipation of the human to rise and rise himself, to humanize.